Preparation of Spray-Dried Soy Isoflavone-Loaded Gelatin Microspheres for Enhancement of Dissolution: Formulation, Characterization and in Vitro Evaluation - Gean Pier Panizzon; Fernanda Giacomini Bueno; Tânia Ueda-Nakamura; Celso Vataru Nakamura; Benedito Prado Dias Filho (MDPI AG, 2014)
The most bioactive soy isoflavones (SI), daidzein (DAI) and genistein (GEN) have poor water solubility, which reduces their bioavailability and health benefits and limits their use in industry. The goal of this study was to develop and characterize a new gelatin matrix to microencapsulate DAI and GEN from soy extract (SE) by spray drying, in order to obtain solid dispersions to overcome solubility problems and to allow controlled release. The influences of 1:2 (MP2) and 1:3 (MP3) SE/polymer ratios on the solid state, yield, morphology, encapsulation efficiency, particle size distribution, release kinetics and cumulative release were evaluated. Analyses showed integral microparticles and high drug content. MP3 and MP2 yield were 43.6% and 55.9%, respectively, with similar mean size (p > 0.05), respectively. X-ray diffraction revealed the amorphous solid state of SE. In vitro release tests showed that dissolution was drastically increased. The results indicated that SE microencapsulation might offer a good system to control SI release, as an alternative to improve bioavailability and industrial applications.